2004
DOI: 10.1194/jlr.m400152-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the gene encoding lipoprotein lipase in men with low HDL-C and coronary heart disease

Abstract: Our goal was to further define the role of LPL gene polymorphisms in coronary heart disease (CHD) risk. We determined the frequencies of three LPL polymorphisms (D9N, N291S, and S447X) in 899 men from the Veterans Affairs HDL Intervention Trial (VA-HIT), a study that examined the potential benefits of increasing HDL with gemfibrozil in men with established CHD and low high density lipoprotein cholesterol (HDL-C; р 40 mg/dl), and compared them with those of men without CHD from the Framingham Offspring Study (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 42 publications
1
16
0
1
Order By: Relevance
“…One of the study of S447X variant in a general population showed the allele frequencies of 0.875 and 0.125 for 'S' and 'X' respectively [30]. These findings are similar to that of the present study, while in another study 'X' allele frequency was found to be 0.06, with a carrier frequency of 13 % in men with low-HDL-C level and with CHD [31].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…One of the study of S447X variant in a general population showed the allele frequencies of 0.875 and 0.125 for 'S' and 'X' respectively [30]. These findings are similar to that of the present study, while in another study 'X' allele frequency was found to be 0.06, with a carrier frequency of 13 % in men with low-HDL-C level and with CHD [31].…”
Section: Discussionsupporting
confidence: 90%
“…A significant increase only in HDL-C was observed by Fujiwara et al [30] in carriers than wild type for LPL S447X variant in Mima general population. Brousseau et al [31] found no significant difference in TC, HDL-C, LDL-C and TG in carriers than wild type for this variant in men with low HDL-C level and with CHD.…”
Section: Discussionmentioning
confidence: 95%
“…In association studies, although the X447 allele has been reported to be associated with a favorable lipid profile in some studies [7][8]22] the results have not been confirmed in other studies [15]. Similarly, the association of the S447X polymorphism with CAD is inconsistent [10][11][12][13][14][15][16][17][18]. In a meta analysis the association of the S447X polymorphism with TG/HDL-C and CAD was found to be small compared to three other LPL amino acid polymorphisms examined [23] or it was gender-specific [24].…”
Section: Introductionmentioning
confidence: 57%
“…Several common LPL genetic variants have been widely studied, and among them HindIII in intron 8 (T→G at position 481), and S447X in exon 9 are of particular interest because of their common occurrence (25% and 9% of the less common alleles, respectively in most populations) and their associations with plasma lipid profile [6][7][8][9][10][11] and susceptibility to CAD [10][11][12][13][14][15] in several studies, although some inconsistent results have also been reported [16][17][18]. Since the HindIII polymorphism is located in the middle of intron 8, it is not considered to be functional but rather in linkage disequilibrium with a putative functional variant.…”
Section: Introductionmentioning
confidence: 99%
“…However, Hallman et al (10) did not find any association between the HindIII(-) allele and higher LPL activity. The associations of certain polymorphic loci in the LPL promoter, introns or exons with lipid disorders and coronary artery disease (CAD) have been reported by some groups (rs285, rs1800590, rs320, rs268, rs1801177) (6)(7)(8)(11)(12)(13)(14) but contested by other authors (15)(16)(17). To the best of our knowledge, no data on the screening of such specific polymorphisms in the Saudi population have been reported.…”
Section: Introductionmentioning
confidence: 85%